Variation in sleep and metabolic function is associated with latitude and average temperature in Drosophila melanogaster. Issue 8 (26th March 2018) - Brown, Elizabeth B.; Torres, Joshua; Bennick, Ryan A.; Rozzo, Valerie; Kerbs, Arianna; DiAngelo, Justin R.; Keene, Alex C.
Abstract: Regulation of sleep and metabolic homeostasis is critical to an animal's survival and under stringent evolutionary pressure. Animals display remarkable diversity in sleep and metabolic phenotypes; however, an understanding of the ecological forces that select for, and maintain, these phenotypic differences remains poorly understood. The fruit fly, Drosophila melanogaster, is a powerful model for investigating the genetic regulation of sleep and metabolic function, and screening in inbred fly lines has led to the identification of novel genetic regulators of sleep. Nevertheless, little is known about the contributions of naturally occurring genetic differences to sleep, metabolic phenotypes, and their relationship with geographic or environmental gradients. Here, we quantified sleep and metabolic phenotypes in 24 D. melanogaster populations collected from diverse geographic localities. These studies reveal remarkable variation in sleep, starvation resistance, and energy stores. We found that increased sleep duration is associated with proximity to the equator and elevated average annual temperature, suggesting that environmental gradients strongly influence natural variation in sleep. Further, we found variation in metabolic regulation of sleep to be associated with free glucose levels, while starvation resistance associates with glycogen and triglyceride stores. Taken together, these findings reveal robust naturally occurring variation in sleep and metabolic traits in D. melanogaster, providing a model to investigate how evolutionary and ecological history modulate these complex traits. Abstract : The fruit fly, Drosophila melanogaster, provides a powerful model for investigating the genetic basis of sleep and metabolic regulation; yet, little is known about the ecological or evolutionary factors that underlie variation in these processes. We have characterized a number of sleep‐ and metabolism‐related traits in 24 outbred D. melanogaster populations collected from geographic localities throughout the world.